Pacific island scrapbook - Belcher, Angie; Belcher, Andy. (London : Collins, 2005)
Vanuatu is a country in the Pacific Ocean made up of lots of tropicak islands. Amy went there on holiday and she made a scrapbook of all the things she saw and did. Find out what you might see if you went there.
Purple Band 8.
Keywords: Islands of the Pacific; Vanuatu